Secondary School Teachers Don’t Have Time to Engage in the Most Important Aspects of Information Literacy Due to Curricular Pressures. A Review of: Williams, D. and C. Wavell. “Secondary School Teachers’ Conceptions of Student Information Literacy.” Journal of Librarianship and Information Science 39.4 (2007): 199-212. - Lotta Haglund (Evidence Based Library and Information Practice, 2009)
Objective – To examine school teachers’ understanding of student information literacy and to look at the implications of the findings for developing information literacy in students. Design – Qualitative research design (group discussions; verbal and written reflections). Setting – Secondary schools in the United Kingdom. Subjects – Secondary school teachers with various subject specializations. Methods – The study initially involved 31 secondary school teachers; 24 from seven schools in Scotland and seven from two schools in England. Participant teachers were self-selecting. The study took a phenomenographic approach. Teachers’ perceptions of their students’ abilities and their experiences and perceptions of their role in developing these abilities were examined through data collection in three stages. During the first stage, group discussions established the teacher’s initial conceptions of information literacy. Participants also filled out an information task grid which, together with focus questions, ensured that discussions were kept in the realm of practice. During the second stage of data collection, teachers observed and reflected on their students’ use of information in classroom activities. This was accompanied by informal site visits during which 26 of the participants were introduced to information literacy frameworks and definitions in order to contextualize reflections and discussions. Field notes were used to record these informal meetings. Six participants provided written feedback on reflections. In the third and final stage, a summary of themes from the first two stages was sent to 23 of the participants prior to a second group discussion in order to try to stimulate further reflection. Discussions were audio recorded and transcribed. The transcribed data were analyzed for the dimensions of variation of teachers’ conceptions of student information literacy and key elements associated with each category of description were determined. Main Results – The data revealed six main conceptions of student information literacy among the teachers: “finding information,” “linguistic understanding,” “makingmeaning,” “skills,” “critical awareness ofsources,” and “independent learning.” There was no particular hierarchy in their conceptualization, although independent learning seemed to be the ultimate goal. Teachers’ conceptions in the beginning ofthe study focused on the ability to find information, whereas after a period of reflection and further discussions, a broader and more complex understanding of information literacy appeared. Table 1 simplifies some of the data from the table in the article and shows conceptualizations as well as some of the contextual elements. Teachers felt that they had at least some control over the development of student ability to find information, develop skills, and critically appraise sources, even though these were not the highest learning priority outcomes. However, in the three areas of ability which the teachers regarded as of high learning priority (linguistic understanding, making meaning and independent learning), they felt that they had little control over the development of these abilities in the students. Conclusion – The teachers’ conceptions of student information literacy overlapped with the ideas in existing models and frameworks for information literacy. However, some areas of information literacy were not addressed by the teachers, i.e., ethical issues in the use of information. In the categories of description of high learning priority, the main reason for the low sense of control by the teachers seemed to be curricular pressures – “our content is prescribed and time allocated doing each of these things is prescribed so we have got limited room for maneuvering” (206). The teachers tended to regard information literacy as process and skills-orientated, with little connection to learning. The authors note that other research also suggests that school librarians also have difficulty relating information finding to learning in specific subject disciplines. There is a clear gap here as the authors point out that “there is a danger that students will not understand the significance of learning with information for academic achievement or for independent learning” (209).The authors suggest that the way forward for further development of information literacy in the classroom and library is through dialogue and that “librarian-teacher collaborations needs to be founded on shared understanding of the complex inter-relationship between information and learning” (209).